Identification, description, and perceptions of personal and professional attributes for student teachers in school health education and rankings of knowledge, skill, and disposition elements within each attribute : a pilot study - Randal, Patricia L. (My University, 2002)
Selecting personal and professional attributes for student teachers in school health education can be difficult for health educators due to the number of attributes important for successful teaching. The problem of this study was to gather judgments from health educators currently teaching in relation to what personal and professional attributes student teachers need to possess when entering their student teaching experience. After the panel of health educators determined the attributes, they had an opportunity to determine which knowledge, skill and disposition elements were most important to have. The invited sample consisted of 63 health educators who are currently teaching health education. The sample was gathered from four different counties in Wisconsin. The overall response rate was 9.5% (N = 6). A modified two round Delphi Technique was used for data collection, along with a nominal rating process. Questionnaire development was based on a list of personal and professional attributes identified through a review of the literature, and suggestions made by the panel of health educators during the first round of the Delphi. Panel members clarified and revised the attribute descriptions during the first round of the study. Each personal and professional attribute consisted of knowledge, skill and disposition elements that-were then ranked using a nominal rating process. Ten personal and professional attributes were identified, clarified, and rated.
Keywords: Health education; Personality assessment; Student teachers - Psychology; Teachers - Training of